STUDI KOMPARATIF NILAI-NILAI ADAB MAKAN, BERPAKAIAN, DAN TIDUR DALAM KITAB MINHAJUL MUSLIM KARYA SYEKH ABU BAKAR JABIR AL JAZAIRI DAN AKHLAQ LIL BANAT KARYA UMAR BIN AHMAD BARADJA - Munadiyan, Luluk; Khoir, Mulyanto Abdullah; Rochmawan, Alfian Eko (Al’ulum Jurnal Pendidikan Islam, 2024)
One of the issues faced by many students today is the lack of attention to ethics and manners, particularly in matters of food and clothing. This problem is influenced by various factors, including the influence of non-Islamic fashion education. This study aims to compare the values of etiquette in eating, dressing, and sleeping as presented in the works of Sheikh Abu Bakar Jabir Al-Jazairi and Umar bin Ahmad Baradja. By analyzing the guidelines provided by these two scholars, the research seeks to identify similarities and differences in their approaches to educating Muslims about manners and morals. The study employs a library research methodology, utilizing both primary and secondary sources. The research is descriptive and qualitative, aiming to describe and interpret the objects based on the data collected, which is then analyzed using content analysis techniques. The findings indicate that "Minhajul Muslim" is intended for a general audience and presents comprehensive values of etiquette, while "Akhlaq Lil Banat" focuses on delivering advice specifically to women, with detailed and concise emphasis on modesty and social ethics.